Formalisasi syariat islam di Indonesia: Tinjauan historis - Ahmad Asroni (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
This study analyzes the history of the formalization of Islamic sharia in Indonesia from the Islamic kingdom era to the reform era. The focus of the study includes how Islamic sharia was implemented in various periods, starting from the Islamic kingdom, colonial era, post-independence, New Order period, to post-reform. This research uses library research method with historical-critical analysis of books, academic journals, historical documents, laws and regulations, and previous research. The results show that the formalization of Islamic sharia has undergone various forms of adaptation and transformation. During the Islamic kingdom period, sharia was applied in criminal law and royal administration. In the colonial era, Islamic law was recognized in the family sphere through religious courts, although its jurisdiction was limited. The Japanese occupation saw formalization through the Shūmubu as a political tool. Post-independence, there was a debate between Islamic and nationalist groups over the basis of the state, followed by the DI/TII rebellion that sought to establish an Islamic state. In the New Order era, although Islamic political policies tended to be repressive, the 1990s saw the accommodation of Islamic law in the regulation of marriage, Islamic banking and zakat. Reform brought new opportunities with the emergence of sharia-based regional regulations along with decentralization. This study shows that the formalization of Islamic sharia in Indonesia is dynamic and influenced by political, social, and legal factors in each era.